Regulating vertical domains distribution in ruddlesden-popper perovskites for electroluminescence devices - Yantara, Natalia (2020)
Efficient perovskite light emitting diodes are designed by employing an ordered vertical domain distribution in quasi 2D perovskites to induce better electron flow to the emitting domains. DMSO is added to the precursor solution to tune the crystallization rate and promote the formation of high m domains near the substrate surface via the one step deposition method. Optimized deposition conditions yielding film with favorable energetic landscape for both carrier injection and confinement results in a fourfold EQE enhancement with maximum EQE of 5.79%. Better carrier injection is further supported by turn on voltage value that is comparable to the bandgap of the emitter material (~2.25 eV).